Affective and developmental transitions: qualitative themes in multicultural counseling journals. Issue 1 (4th January 2016) - Mayes, Renae D.; Dollarhide, Colette T.; Marshall, Bowen; Rae, Alexis
Abstract : Purpose: – The purpose of this paper is to examine how multicultural counseling students expressed their understandings about themselves and others in relation to diversity. The authors wanted to know how cognitive development, affective development, and sense of self-evolved during a multicultural counseling class to examine all aspects of growth. Design/methodology/approach: – Themes from a phenomenological qualitative analysis of journals from a multicultural counseling class suggest that students struggle with cognitive challenges (dealing with ambiguity, internalizing multicultural concepts, and self- and other-acceptance) and affective challenges (anger, guilt, and fear) in attaining multicultural growth. Findings: – This expanded view of multicultural growth that includes affective challenges can fill a prior gap in understanding how multicultural learning occurs. Research limitations/implications: – Implications are explored for counselor educators and supervisors. Originality/value: – Recent use of journals to provide empirical insights into student growth include a study by Cohen et al. (2015), who used qualitative analyses of journal contents to examine growth in student attitudes toward geriatric clients, death, and dying. Knowing that student journals can provide insights into changing multicultural attitudes, and that qualitative methodology can provide tools for analysis, the authors decided that it might be possible to better understand multicultural growth by studying the journals written in a multicultural counseling class.